Research Policy - Machakos university (My University, 2018)
Machakos University has a strong technical background and has therefore built a unique niche in training technical personnel in diverse areas of Civil Engineering, Electrical and Electronics Engineering, Fashion Design and Marketing, Hospitality & Tourism, Business, Education, Agribusiness and Applied Sciences. These areas also generate researches that inform new discoveries, trends and innovation that need a strong foundation. This research policy has therefore been developed to help the university to remain on track in developing programmes with orientation towards Science, Technology and Innovation, and thus contributing towards the attainment of Vision 2030 and the Sustainable Development Goals (SDGs). Thus, the central goal of the Machakos University Research Policy is to help the institution remain true to its philosophy, “to provide transformative leadership in Teaching, Training, Research, Innovation, Industrial and Technology transfer for wealth creation”. This philosophy is firmly anchored in Machakos University’s research orientation as encapsulated through its mission: “to provide scholarly education through Training, Research and Innovation for Industrial and socio-economic transformation of our communities”. Indeed, this policy prescribes the guidelines that will govern research funds and their administration, ethical aspects, publication and dissemination, intellectual property and copyright issues, and monitoring and evaluation among other critical issues on research. It is my sincere hope that the university will embrace the policy and utilise it to facilitate the furthering of Machakos University research goals. Prof. Lucy Irungu, PhD Vice- Chancellor & Professor of Entomology